Frenulectomy in the Treatment of Diastema - N. Grégrová; P. Černochová (Czech Dental Chamber, 2011)
Introduction: Diastema mediale is quite a frequent phenomenon. At a certain stage of development of the jaws and eruption of teeth, it can be regarded as a physiological phenomenon. If diastema persists also in the permanent dentition, it becomes orthodontic anomaly. Many factors are applied in its etiology. Often is considered a cause the deep insertion of the upper lip frenum (frenulum labiale). Therefore, it is sometimes in its therapy suggested frenulectomy or frenotomy. Objective: To summarize the range of views on the importance frenum in the etiology of the diastema and on the importance of the frenulectomy in its treatment, which are reported in the literature. Material and methods: It was used for the searching for scientific articles Metalib program, through which were carried out searches in the databases: PubMed, Medline (Ovid), Lippincott Williams & Wilkins (LWWonline) (Ovid), Evidence-Based Medicine, Biological Abstracts. It also was used Google Scholar with granted access to electronic resources Masaryk University (MU). Additional sources were obtained by searching the bibliographies of available full-text articles and searching in journals and monographic publications available in the library at MU. Results: The survey includes 13 articles and 8 monographic publications corresponding to the required criteria. Conclusion: The literature review shows a great difference of opinion in view of the indication of frenulectomy in the treatment of diastema. Most authors recommend a prudent approach based on individual assessment of the causes of diastema, possibility of spontaneously modification of deep attachment of frenum during orthodontic tooth movement and growth of the alveolar process and the need of retention.